Digital transformation of public financial management: A case study of regional financial application integration in North Sulawesi - Junior Lakat (Privietlab, 2025)
Local governments in Indonesia face the challenge of improving efficiency, transparency, and accountability in public financial management. One of the strategic efforts undertaken is the digital integration of regional financial applications. However, the success of this transformation depends not only on the technology itself but also on users’ perceptions regarding usefulness, ease of use, and perceived risk. This study aims to analyze the influence of Perceived Usefulness, Perceived Ease of Use, and Perceived Risk on the effectiveness of public financial management through the integration of regional financial applications in North Sulawesi. A quantitative approach was employed by distributing questionnaires to 70 respondents who are users of the financial application in regional government institutions. Multiple linear regression was used for analysis, along with classical assumption tests such as normality, multicollinearity, and heteroscedasticity, followed by t-test and F-test for significance testing. The findings indicate that Perceived Usefulness, Perceived Ease of Use, and Perceived Risk each have a significant partial and simultaneous effect on public financial management. Among them, Perceived Ease of Use exerts the strongest influence, followed by Perceived Usefulness and Perceived Risk. Interestingly, in contrast to previous research suggesting that risk negatively impacts technology adoption, this study finds that Perceived Risk has a positive and significant influence. This suggests that risk awareness can promote more careful and responsible use of financial systems without reducing their effectiveness. Digital transformation in public financial management is shaped not only by infrastructure but also by user perceptions. Perceived usefulness, ease of use, and risk are crucial in supporting the success of regional financial application implementation. Transformation strategies must therefore be supported by organizational readiness and enhanced digital literacy among public officials.